Realization of Communicative Strategies and Tactics through Using the Auto-Ethnonym “Russian” - K. A. Sukhareva (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The results are presented of the study of the mechanisms of realizing the communicative strategies and tactics in Russian advertising discourse, the language representative of which is auto-ethnonym Russian and corresponding derivatives. The interest to the phenomenon of discourse is linked both with the need to study linguistic phenomena in close connection with communicative, cognitive and sociocultural factors, and with the need to bring linguistic research beyond the study of traditional units of sentence and text. The need for a theoretical understanding of the specificity of advertising discourse is linked to the active development of this type of discourse and its increasingly prominent place in the modern communicative space. The novelty of the research is to analyze the functioning of auto-ethnonymic lexis in advertising discourse, which until this time was not the object of researchers in this aspect. The material were taken from advertising slogans and texts of Russian advertising discourse. Peculiarities of advertising communication is described, main positioning of communicative strategy: auto-presenting, evaluative, targetising, mitigative, value-oriented - are analyzed. Some optimizing communication strategies are discussed: the strategy of recognition and the strategy of increasing attractive strength of the advertising message. The practical significance of the research is connected with the possibility to apply its results in practice of creating advertising messages and in judicial and non-judicial linguistic expert investigations in cases of improper advertising and extremism.